A Catalog of Galaxy Clusters Identified from SCUSS, SDSS, and UNWISE. (13th January 2020) - Gao, Jinghua; Zou, Hu; Zhou, Xu; Kong, Xu
Abstract: This paper presents the identification of galaxy clusters from the photometric redshift catalog based on three imaging surveys of SCUSS, Sloan Digital Sky Survey, and unWISE. By applying a fast clustering algorithm, we obtain a total of 19, 610 clusters in the redshift range of 0.05 <  z  < 0.65 over a sky area of about 3700 deg 2 in the south Galactic gap. Monte Carlo simulations show that the false detection rate is about 8.9%. The redshift uncertainty is estimated to be about 0.013. The mass and richness of detected clusters are derived through the calibration based on the measurements of X-ray emission and Sunyaev–Zel'dovich effect. The median mass is 1.2 × 10 14 M ⊙ .